Timing optimization of teriparatide dosing for postmenopausal osteoporosis: a randomized controlled trial - Huan Wang; Liyuan Tao; Dongyang Liu; Xiaoyan Yan; Haiyan Li; Chunli Song (Journal of Orthopaedic Surgery and Research)
Abstract Background Accumulating evidence highlights the critical role of circadian rhythms in regulating bone turnover. Bone turnover markers, including parathyroid hormone, C-terminal telopeptide of type I collagen, and N-terminal propeptide of type I procollagen, all exhibit distinct diurnal variations. Teriparatide, a recombinant parathyroid hormone analog, demonstrates time-dependent efficacy influenced by these endogenous rhythms. However, the impact of administration timing on bone metabolism remains underexplored. Objective This randomized, open-label, exploratory trial investigates the impact of teriparatide administration timing by comparing subcutaneous injection at 08:00 versus 20:00 on bone turnover markers in postmenopausal women with osteoporosis. Methods Twenty-eight participants (aged 60–70 years, lumbar spine T-score ≤ -3.0) will be randomized in a 1:1 ratio to receive 20 µg/day of teriparatide via subcutaneous injection at either 08:00 or 20:00 for 12 weeks. All participants will receive standardized calcium (1000–1500 mg/day) and cholecalciferol (800–1200 IU/day) supplementation throughout the study period. The primary outcomes are the between-group differences in serum parathyroid hormone, C-terminal telopeptide of type I collagen, and N-terminal propeptide of type I procollagen profiles, which will be assessed at baseline, 4 weeks, and 12 weeks. Secondary outcomes will evaluate the safety profile during the trial. Discussion This trial is expected to provide crucial insights into optimizing teriparatide administration timing, potentially guiding personalized dosing strategies to enhance bone formation and reduce fracture risk in osteoporosis. The findings may inform future research on circadian rhythm-aligned therapies. Trial registration ClinicalTrials.gov ID NCT06951776.